Islamic Civilization According to Muhammad Fethullah Gulen - Miftah Ahmad; Nabila Huringiin; Umi Nur Hasanah (Tasfiyah: Jurnal Pemikiran Islam, 2021)
This article describes the confusion of the West phenomenon which is often declared by the glorious civilization according to modern society. But, Islam as a great religion is known to be a backward civilization and left behind from the West. A Turkish scholar named Muhammad Fethullah Gulen observed this phenomenon and tries to declare that the Islamic civilization is not backward. This type of research is library research, listing all literature and data related to Gulen’s perspective in the concept of Islamic civilization development. Researchers used descriptive-analysis methods to describe and analyze the concept of Islamic civilization according to Gulen and how to build it. The Researcher concludes that the pillars of Islamic civilization according to Muhammad Fethullah Gulen include four pillars, moral-spiritual, aesthetics, and love for the Creator.